Oczekiwania komunistycznych władz wobec kobiet : działalność Ligi Kobiet na Dolnym Śląsku w latach 1950–1960 - Trzaskowska, Grażyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article aims at depicting the position and role of women in socialist society in the context of the policy the authorities adopted towards the activities of Liga Kobiet (the Women’s League) in Lower Silesia. The main focus is placed on the issue of determining the degree to which the association was a movement for the benefit of women, or an organization that carried out tasks imposed from the top down, which served to legitimize the communist authorities. The article presents the standpoint of the authorities concerning the women’s movement and its evolution against the background of transitions that took place in Poland between 1950 and 1960. In the aforementioned timeframe two periods of Liga Kobiet’s activity may be distinguished. The first period is framed by the dates of the fulfillment of the six-year plan and the Polish thaw of October 1956; the second – by the transformations in the aftermath of the Polish thaw and the jubilee year of 1960, which prompted reflection and the drawing of conclusions. During the initial period attempts to subjugate the women’s movement to the demands of communist ideology were made, while the second period was characterized by a turn towards women and their social needs
Keywords: Liga Kobiet; kobiety; aktywistki; koła gospodyń wiejskich; współzawodnictwo pracy; mobilizacja; kursy gospodarstwa domowego; szkolenia zawodowe; praca chałupnicza